Waste reduction using lean tools in a multicultural environment. (20th August 2020) - Purushothaman, Mahesh babu; Seadon, Jeff; Moore, Dave
Abstract: There is a significant body of knowledge linking lean tools to waste reduction. This research considered system-wide relationships that enabled lean tools to aid waste reduction in industrial processes in a multicultural workplace environment in organisations that previously committed to Lean practices. Ten categories of waste prevalent in industry were categorised into manufacturing, non-manufacturing and well-being. Seven case studies from five companies were conducted which sought to establish the relationship between lean tools and waste in their processes. The study was based on interviews that highlighted the positive and negative impacts that lean tools have on waste. The study generally found a strong connectivity between lean tools and manufacturing waste reduction. However, the key performance indicators (KPIs) tool increased non-manufacturing waste and six lean tools increased well-being waste. Additionally, the findings indicate that some tools can be counter-productive to waste reduction in an industrial system when non-manufacturing and well-being are taken into account. Lean tools were resilient enough that implementation in multicultural workplaces, even with transient populations, did not influence waste generation. Highlights: Identified system-wide relationships that enabled lean tools to aid waste reduction in industrial processes in a multicultural workplace environment. Ten categories of waste prevalent in industry were categorised into manufacturing, non-manufacturing and well-being. The study highlighted the positive and negative impacts that lean tools have on waste. Study demonstrates that lean tools were resilient enough that implementation in multicultural workplaces, even with transient populations, did not influence waste generation. System wide approach to plot lean tools and waste relationship.